Influence of a tropical grass (Brachiaria brizantha cv. Mulato) as cover crop on soil biochemical properties in a degraded agricultural soil - Perez Brandan, Carolina; Chavarria, Diego N.; Huidobro, Dina Jorgelina; Meriles, Jose Manuel; Perez Brandan, Cecilia Maria; Vargas Gil, Silvina (Elsevier, 2018)
The inclusion of tropical grass forage as a cover crop (CC) could be a useful tool to improve microbiological activity and, consequently, soil quality. The aim of this study was to evaluate the effect of Brachiaria brizantha cv. Mulato and maize (Zea mays) as CC on soil microbial communities and their contributions to a degraded common bean (Phaseolus vulgaris L.). monoculture system. Soil sampling was carried out in 2016 after six years of cumulative effect across different treatments: B. brizantha-B. brizantha-common bean (B2), B. brizantha-common bean (B1), maize-common bean (M) and common bean monoculture (control). B2 and B1 showed higher fluorescein diacetate hydrolysis (108.1% and 78.6%, respectively) and higher acid phosphatase activity (304.5% and 181.6%, respectively) compared with the control treatment. The metabolic efficiency was higher in treatments containing B. brizantha as CC, with a significantly lower metabolic quotient (respiration rate per unit microbial biomass carbon) in B2 (1.65) compared with the control (5.46). The B2 treatment also showed higher values of soil organic carbon, which was correlated with soil microbial activities. In contrast, qPCR analysis of microbial structure did not show significant differences in response to the evaluated treatments. Thus, fungal and bacterial abundance probably had less influence on the differentiation of treatments compared to microbial activity and soil chemical properties. In context of this research, the use of B. brizantha as CC increased soil fertility and generated a greater microbial metabolic efficiency. Our research demonstrates that B. brizantha cv. Mulato as CC is a suitable agricultural tool to restore soil biochemical properties.